PENGARUH BULLYING TERHADAP KETERAMPILAN SOSIAL SISWA KELAS IV SD NEGERI 060934 MEDAN JOHOR - Tesalonika Br Tarigan; Reflina Sinaga; Rumiris Lumban Gaol; Ester Julinda; Antonius Remigius Abi; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of bullying on social skills of fourth grade students of SD Negeri 060934 in the 2023/2024 learning year. This study is motivated by the low social skills behavior of students due to bullying in class IV SD. This type of research is quantitative research. The type of sample used in this study is a saturated sample. The samples used were fourth grade students totaling 30 students. Based on the results of the study, it shows that there is an influence of bullying on social skills on fourth grade students of SD Negeri 060934 in the 2023/2024 learning year from testing the correlation coefficient, it is concluded that the alternative hypothesis (Ha) is accepted, where there is a positive and significant influence between bullying behavior on students' social skills, seen from the results of the t-test test which is (20.264 1.697), then Ha is accepted. This shows that there is an influence of bullying on social skills on fourth grade students of SD Negeri 060934 in the 2023/2024 learning year.